Differential Recruitment of Dendritic Cells Subsets to Lymph Nodes Correlates with a Protective or Permissive T-Cell Response during Leishmania (Viannia) Braziliensis or Leishmania (Leishmania) Amazonensis Infection - A. K. Carvalho; K. Carvalho; L. F. D. Passero; M. G. T. Sousa; V. L. R. da Matta; C. M. C. Gomes; C. E. P. Corbett; G. E. Kallas; F. T. Silveira; M. D. Laurenti (Mediators of Inflammation)
Leishmania (L.) amazonensis (La) and L. (V.) braziliensis (Lb) are responsible for a large clinical and immunopathological spectrum in human disease; while La may be responsible for anergic disease, Lb infection leads to cellular hypersensitivity. To better understand the dichotomy in the immune response caused by these Leishmania species, we evaluated subsets of dendritic cells (DCs) and T lymphocyte in draining lymph nodes during the course of La and Lb infection in BALB/c mice. Our results demonstrated a high involvement of DCs in La infection, which was characterized by the greater accumulation of Langerhans cells (LCs); conversely, Lb infection led to an increase in dermal DCs (dDCs) throughout the infection. Considering the T lymphocyte response, an increase of effector, activated, and memory CD4+ T-cells was observed in Lb infection. Interleukin- (IL-) 4- and IL-10-producing CD4+ and CD8+ T-cells were present in both La and Lb infection; however, interferon- (IFN-) γ-producing CD4+ and CD8+ T-cells were detected only in Lb infection. The results suggest that during Lb infection, the dDCs were the predominant subset of DCs that in turn was associated with the development of Th1 immune response; in contrast La infection was associated with a preferential accumulation of LCs and total blockage of the development of Th1 immune response.